What do we know about the labor share and the profit share? Part III: Measures and structural factors - Olivier Giovannoni (Levy Economics Institute of Bard College, 2014)
Economic theory frequently assumes constant factor shares and often treats the topic as secondary. We will show that this is a mistake by deriving the first high-frequency measure of the US labor share for the whole economy. We find that the labor share has held remarkably steady indeed, but that the quasi-stability masks a sizable composition effect that is detrimental to labor. The wage component is falling fast and the stability is achieved by an increasing share of benefits and top incomes. Using NIPA and Piketty-Saez top-income data, we estimate that the US bottom 99 percent labor share has fallen 15 points since 1980. This amounts to a transfer of 1.8 trillion from labor to capital in 2012 alone and brings the US labor share to its 1920s level. The trend is similar in Europe and Japan. The decrease is even larger when the CPI is used instead of the GDP deflator in the calculation of the labor share.
Keywords: D33; E24; E25; 330; Labor Share; Composition Effect; Income Inequality; Top Incomes; Purchasing Power